PROBLEMATIKA KETERAMPILAN BERBICARA PESERTA DIDIK SEKOLAH DASAR - Ernamasari, Navalia Dewi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The purpose of the study is to determine and examine the problems pertaining to elementary school pupils' speaking abilities. A qualitative descriptive case study is the research methodology employed. Twenty-six third-graders and one homeroom teacher from SDN Brangkal 1 in Gemolong District, Sragen Regency, serve as the research subjects.The techniques and tools used for data collection were observation and interviews with students and teachers.The analysis technique used is qualitative with the stages of data reduction, data display, and conclusion drawing.The research results show that the problems with students' speaking skills include (1) lack of self-confidence, (2) limited vocabulary, (3) speaking mixed with regional languages, (4) students not understanding the content of the conversation, (5) incorrect placement of tone and intonation, and (6) poor speaking etiquette.This research also provides recommended solutions to address these issues, including (1) the implementation of teaching methods that can enhance students' speaking skills, (2) the organization of public speaking. training, (3) the development of learning media, (4) the application of Peer Lessons strategies, (5) a communicative approach, and (6) the analysis of factors causing speaking difficulties